Ethical Aspect of Infertility Treatment through Surrogacy based on Utilitarian Principle: Surrogacy & utilitarianism - Nazari Tavakkoli, Saeid; Karachian Sani , Fatemeh (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: One of the questions that may be raised about infertility treatment through surrogacy is the ethicality of this approach. There are many methods for the ethical clarification of the medical issues. If we accept the utilitarian philosophers’ views stating that an ethical measure is beneficial to the community and individuals, we may come up with the question whether the actions of the infertile couples or surrogate mother are considered ethical since these actions are beneficial for both individuals and community. Regarding this, the present study aimed to evaluate the infertile treatment through surrogacy based on the ethical theories of utilitarianism. Materials and Methods: This analytical-descriptive research gathered relevant data in a literature search. After a description of the fundamentals and definitions, ethical texts were subsequently analyzed and one of the viewpoints regarding of Infertility Treatment through Surrogacy Based on Utilitarian Principle was selected. Ethical Considerations: Ethical principles were considered in searching and citing the literature. Findings: According to the rule utilitarianism, the ethicality of an action is measured based on its collective benefit and its placement in an ethical principle framework. Therefore, we cannot treat surrogacy like an accepted ethical principle, such as sacrifice, and provide a general rule for the determination of the effect of different social, cultural, economic, and political factors on the people involved in this act. However, the use of this method in different situations and for various people could be very beneficial and be considered ethical. Conclusion: Although the comprehensive investigation of the harmful use of surrogacy has not been accomplished, the various problems and factors affecting the evaluation of the overall profit and loss of this act grab the possibility of determining its morality as a valid rule in the rule-based ethics. However, such a provision is justified in the utilitarian and pragmatic ethical systems. *Corresponding Author: Saeid Nazari Tavakkoli; Email: sntavakkoli@ut.ac.ir; ORCID: https://orcid.org/0000-0002-6398-521X Please cite this article as: Nazari Tavakkoli A, Karachian Sani F. Ethical Aspect of Infertility Treatment through Surrogacy based on Utilitarian Principle. Bioeth Health Law J. 2021; 1:1-8: (e17). http://doi.org/10.22037/bhl.v1i1.38171